Disentangling an avian assemblages’ evolutionary and functional history in a Chihuahuan desert city - Vital Garcia, Cuauhcihuatl (2019)
Urban green spaces have been shown to be important hotspots of biodiversity in cities of temperate and humid/semihumid tropical ecoregions. Nonetheless, whether this pattern applies to urban ecosystems of desert environments has been rarely studied. Temperature, precipitation, vegetation complexity, human density, and presence of invasive species could act as urban filters limiting the incidence of desert-adapted species into cities. Such effects could be reshaping biotic communities, favoring habitat generalist species in human-dominated environments. In this study, we examined the phylogenetic and functional structure of avian assemblages in a Chihuahuan desert city and its surroundings to infer the processes underlying community assembly. We used phylogenetic comparative methods to test the hypothesis whether there is an underlying pattern determining which desert-adapted species penetrate or tolerate a novel urban ecosystem. We also performed a regression approach to determine which environmental and anthropogenic variables may be associated with these metrics. We found that urban green spaces present more evolutionary and functional diversity (based on the proportion of total tree branch length) than agricultural fields and desert scrub, although not statistically significant. On the other hand, based on the mean branch length distance among sample taxa, we observed clustered communities suggesting environmental filtering. Most continuous functional traits presented a low and significant phylogenetic signal, but nearly all binary traits were conserved across phylogeny. Phylogenetic predisposition to be a habitat generalist is present in the surveyed avian assemblages. Our regression analysis indicates that invasive bird species richness was negatively correlated with net relatedness index (NRI) and functional net relatedness index (FNRI), while functional diversity metrics were influenced by temperature and precipitation